Legal Mutilation and Moral Exclusion: Disputations on Integrity and Deformity in Early China. - Galvany, Albert; Graziani, Romain (T'oung Pao, 2020)
This article examines attitudes evidenced in pre-imperial and Han sources (ritual compendia, historical chronicles, legal codes, administrative texts, and philosophical literature) towards visually repulsive individuals, in particular those who have undergone a penal mutilation. We start from the perception of bodily harm in the light of legal and ritual norms and the moral imperative of physical integrity, and then set out to analyze the concrete outcomes of mutilation visited upon certain kinds of offenders. Finally, we focus on three stories in the Zhuangzi , whose imaginary dialogues illustrate the way their authors try to change the social perception of outcasts in a context that was clearly adverse to their possible rehabilitation.